Analyzing Drought Propagation and Its Influential Factors in the Upper Nan Watershed, Thailand - Muhammad Chrisna Satriagasa; Piyapong Tongdeenok; Naruemol Kaewjampa (Environment and Natural Resources Journal)
Understanding drought propagation is essential for effective water resource management. This study employs an innovative approach to examine the transition from meteorological drought (MD) to hydrological drought (HD) in the Upper Nan Watershed (UNW), Thailand, using the standardized precipitation evapotranspiration index (SPEI) and standardized streamflow index (SSI). Cross-wavelet transform (XWT) and Pearson’s correlation analyses reveal a significant positive correlation between MD and HD, with the drought propagation time (DPT) ranging from 2 to 5 months, notably shorter during the dry season. The eastern UNW (Zone I) has the longest DPT, while the western UNW (Zone III) has the shortest. This study is distinguished by its integration of global teleconnection factors, such as El Niño-Southern Oscillation (ENSO), the Dipole Mode Index (DMI), and Pacific Decadal Oscillation (PDO), alongside local factors like climate, slope, and watershed morphometry. This dual focus provides a comprehensive analysis of drought dynamics, enhancing the understanding of drought propagation and its complexities. The integration of global and local influences provides insights applicable across diverse water resource management contexts. It highlights the critical role of forests in regulating water flow and extending the DPT, emphasizing the need for forest conservation and land use regulation in the headwaters. Despite challenges associated with highland meteorological data, findings offer improvements to existing drought monitoring and early warning systems, underscoring the importance of combining global and local factors in effective drought management strategies.